Needs Analysis for a Community-Based Electronic Learning Management Ecosystem - Blessing O. Akindele (IEEE, 2021)
This paper explains the need for sustainable information-based management technologies for the online community-based ecosystem, its analogies, architecture design, and delivery. Subsequently, this paper describes the benefits of the proposed ecosystem compared to the currently available platforms. Additionally, this article investigates the problems in the systems of two higher learning institutions. Now, the systems used in higher education institutions are disintegrated. The proposed ecosystem objective is to bridge data redundancy and duplication gaps among higher learning institutions. The research methodologies used are document analysis, participant observation and in- depth interviews. This document creates a learning community culture among the five distinguished members: 1) Lecturers, 2) students, 3) administrators, 4) public, and 5) potential employers. Online Community-based Ecosystem (OnCE) is a system created specifically for the learning community culture. The result of the gathered data shows that the OnCE system can impact students’ learning proficiency and positively influence their learning culture. The implication of this research shows that the online community-based ecosystem is essential to support learning and ensure improved facilities, knowledge, and skills, thus preparing graduates before entering the job market, even though courses are taught remotely using educational technology.